Talking black and white : an intercultural exploration of twenty-first-century racism, prejudice, and perception - Bell, Gina Castle (Lexington Books, 2016)
"This book investigates domestic race-related social justice issues and intercultural communication between Black and White individuals. Twenty-first-century racism, racial tensions, prejudice, police brutality, #BLM, misperception, and the role of the past are deconstructed in an engaging, provocative, and accessible manner."--Provided by publisher.